2003
DOI: 10.2754/avb200372040639
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Metabolism in Cattle: Maternal Transfer of Selenium to Newborn Calves at Different Selenium Concentrations in Dams

Abstract: The aim of the study was to investigate the selenium metabolism in the maternal transfer of selenium to newborn calves. For a study, a total of 24 high-pregnant dairy cows at dry-off from two herds with different selenium status were used. While Herd I cows suffered from selenium deficiency, selenium status in cows of Herd II were adequate. Herd I cows were divided into three groups: E1, E2 and C. Selenium-and-vitamin supplement (Selevit inj. a.u.v.) was administered intramuscularly to cows of the E1 group 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
8
26
0
Order By: Relevance
“…In one herd only, slightly lower values in calves were found at the GSH-Px activity above 600 µkat/l. This finding is in agreement with our previous results when we reported a very close correlation between Se concentrations and GSH-Px activity in the blood of newborn calves and their dams (r = 0.91 and 0.93, respectively) (Pavlata et al, 2003). Relatively good results were obtained in cows and their calves, when Se deficiencies were found in 20 and 25% of farms, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In one herd only, slightly lower values in calves were found at the GSH-Px activity above 600 µkat/l. This finding is in agreement with our previous results when we reported a very close correlation between Se concentrations and GSH-Px activity in the blood of newborn calves and their dams (r = 0.91 and 0.93, respectively) (Pavlata et al, 2003). Relatively good results were obtained in cows and their calves, when Se deficiencies were found in 20 and 25% of farms, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Our evaluation of the Se status of cows and their calves has confirmed that the Se status in calves is very similar to that of cows, and if an adequate (or, alternatively, deficient) Se status is found in one of the two groups, it may be assumed that it also applies to the other group (Pavlata et al, 2003(Pavlata et al, , 2004b. Although statistically significant differences between GSH-Px activities in calves and their dams were found on 4 farms, the differences could not have caused a fundamentally wrong interpretation of the Se status, i.e.…”
Section: Discussionsupporting
confidence: 67%
“…This is in contrast to results which have been acquired in cattle. Pavlata et al (2003) found similar levels of selenium in the blood of cows and their calves. Kincaid and Hodgson (1989) also found, in cows with access to selenium-containing lick, that their calves had approximately identical levels of selenium in whole blood as their mothers on the day of delivery.…”
Section: Resultsmentioning
confidence: 68%
“…Levels of microelements in newborns ruminants and their mothers have not yet been studied extensively and thus available information is limited. Most publications on this topic monitor the levels of selenium in cattle (Koller et al, 1984;Kincaid and Hodgson, 1989;Pavlata et al, 2003), or sheep (Langlands et al, 1991). For this reason we monitored the levels of selenium and activity of glutathione peroxidase in goats and their kids.…”
mentioning
confidence: 99%
“…This work goes out from a part of an experiment realised in a framework of an investigation of selenium metabolism in the maternal transfer of selenium to newborn calves (Pavlata et al, 2003). The method in this work is expanded and results are evaluated from the wiev of an influence of selenium and vitamin E on selected metabolic parameters, colostrum quality and state of health.…”
Section: Methodsmentioning
confidence: 99%